GPS Signal Strength Due to Ionospheric Scintillation : Preliminary Models Over Sarawak - Bong, V.P.; Wan Zainal Abidin, W.A.; Abdullah, M.; Kismet, Hong Ping; Masri, T.; Bahari, S.A.; Abba, I. (2015)
The renowned effect of space weather is fluctuation in the amplitude of the radio signal that propagates in the ionosphere especially in the equatorial region. This fluctuation is also referred to as scintillation that will intense, degrades the signal quality, reduce the information content, or cause failure of the signal reception. Space-based radio navigation systems such as the Global Positioning System (GPS) will provide us with a unique opportunity to characterize the ionospheric scintillation effect as the signals propagate from the satellites to the GPS receiver. Sarawak, which is located near to the equatorial region, has been selected for the aim of this research. By using amplitude scintillation data recorded by the GPS Ionospheric Scintillation & TEC Monitor (GISTM), ionospheric irregularities along the path was examined and related to the signal strength performance. Methods and procedures to study and analyze the amplitude scintillation data are presented. Furthermore, the amplitude scintillation parameter is related to signal-to-noise ratio (SNR) in order to model the GPS satellite signal strength in this region. The preliminary developed SNR empirical models are a function of amplitude scintillation from the reference station path to the satellites. These contribute to the knowledge of received satellite signals strength performance in terms of ionospheric amplitude scintillation.